The role of timely initiation of antenatal care on protective dose tetanus toxoid immunization: the case of northern Ethiopia post natal mothers - Muhabaw Shumye Mihret; Miteku Andualem Limenih; Temesgen Worku Gudayu (BMC, 2018)
Abstract Background Globally, tetanus toxoid protective dose immunization of the mothers is one of the strategies of maternal and neonatal tetanus prevention. Ethiopia has planned the national tetanus protection at birth coverage to reach 86% by the year 2015. However, there is still low coverage with less identified associated factors. Therefore; the purpose of this study was to assess tetanus toxoid protective dose immunization at last birth and associated factors among mothers who gave birth within one year prior to the study in Debretabor town, Northwest Ethiopia, 2016. Methods A community based cross sectional study was conducted from May 1 to June 10 / 2016. A total of 511 mothers were included in the study. Structured questionnaire and checklists were used to collect the data. Face to face interview with cross checking documented record were employed. A systematic random sampling technique was used. The data were entered in to Epinfo version 7.0 and then exported to SPSS version 20.0 for analysis. Both bivariate and multivariable logistic regression model were fitted and crude and Adjusted Odds ratio with 95% confidence interval were computed. Finally, statistically significant association of variables was determined based on Adjusted Odds ratio with its 95% confidence interval and p-value ≤0.05. Result The proportion of tetanus toxoid protective dose immunization among mothers was 56.2% (95% CI: 52-60%). In the multivariable analysis; formal education (AOR = 2.09; 95%CI: 1.12, 3.90), planned last pregnancy (AOR = 6.63; 95%CI: 2.36, 18.63), four or more antenatal care visits (AOR = 5.16; 95%CI: 2.93, 11.14), timely antenatal care visit (AOR = 4.29; 95%CI: 1.94, 9.49), and perceived good quality of service (AOR = 2.20; 95% CI: 1.26, 3.84) were positively associated with tetanus toxoid protective dose immunization. Conclusion In this study, protective dose tetanus toxoid immunization is lower than the national target. Strengthening information education communication regarding tetanus and its prevention and encouraging timely initiation of and complete attendance of antenatal care is recommended.